2013
DOI: 10.1016/j.renene.2012.10.040
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for equitable performance assessment and presentation of wave energy converters based on sea trials

Abstract: A general and widely applicable methodology to assess and present the performance of wave energy converters (WEC) based on sea trials is presented. It is meant to encourage WEC developers to present the performance of their WEC prototypes, on a transparent and equitable way while taking care of possible discrepancy in the observed performance of the WEC. Due to the harsh uncontrollable conditions of the sea that is encountered by WECs during sea trials, some of the performance of the WECs might be sub optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Kofoed et al [8,9] provides a method for estimating the uncertainty in MAEP associated with device performance uncertainty, including for situations of limited data. The authors use standard methods for error propagation similar to Livermore and the authors mention that Monte Carlo simulation may be a more robust alternative.…”
Section: Measurementmentioning
confidence: 99%
“…Kofoed et al [8,9] provides a method for estimating the uncertainty in MAEP associated with device performance uncertainty, including for situations of limited data. The authors use standard methods for error propagation similar to Livermore and the authors mention that Monte Carlo simulation may be a more robust alternative.…”
Section: Measurementmentioning
confidence: 99%
“…Within equitable evaluation of marine energy converters, a methodology for equitable performance assessment and presentation of marine energy converters was developed [27]. This methodology was further enhanced and can be found in appended Paper A, B and D [28], [29]. 7…”
Section: Thesis Outlinementioning
confidence: 99%
“…A brief overview of the methodology on how to equitably assess the performance of wave energy converters based on sea trials will be given here. However, a more extended version can be found in the appended paper Assessment and Presentation of Wave Energy Converters Based on Sea Trials [29]. The paper is an elaboration of the EquiMar D4.2 protocol on Data Analysis & Presentation of Marine Energy Converters based on Sea trials [28].…”
Section: Performance Assessment Of Wecs Based On Sea Trials 51 Intromentioning
confidence: 99%
See 1 more Smart Citation
“…A condensed overview of a methodology to equitably assess the performance of wave energy converters based on sea trials will be presented here [22,23] and case studies of it can be found for the Pico OWC and the Wave Dragon WEC [24,25]. The "Equitable Performance Assessment and Presentation" methodology aims at assessing the performance of any device, based on sea trials, in a transparent and equitable way, resulting in an estimation of the mean annual energy production (MAEP) together with a corresponding accuracy.…”
Section: Introductionmentioning
confidence: 99%